Analysis of Risk Factors that Influence Patient Compliance in Taking Antiretroviral Drugs for HIV/AIDS Treatment in Hanoi Hospital, Vietnam - Pham Uyen; Mariette Jackson (Scientific Journal of Dermatology and Venereology, 2024)
Introduction: HIV/AIDS infection remains a global public health problem, with antiretroviral therapy (ARV) being key in its management. Patient adherence to ARV treatment is critical to achieving viral suppression and preventing drug resistance. This study aims to analyze the risk factors that influence patient compliance in taking ARV drugs at Hanoi Hospital, Vietnam. Methods: This study used a cross-sectional analytical observational design involving 300 HIV/AIDS patients undergoing ARV therapy at Hanoi Hospital. Data was collected through structured interviews and patient medical records. Data analysis used logistic regression to identify risk factors associated with patient compliance. Results: The research results showed that the level of patient compliance with ARV treatment was 72%. Risk factors that are significantly associated with patient compliance are: Low social support (OR=2.3; p=0.02), Limited knowledge about HIV/AIDS and ARV treatment (OR=1.8; p=0.04), Stigma and discrimination related to HIV/ AIDS (OR=1.7; p=0.03), Severe side effects of ARV drugs (OR=1.6; p=0.03), Complexity of ARV treatment regimens (OR=1.5; p=0.04). Conclusion: This study found that patient adherence to ARV treatment at Hanoi Hospital was influenced by various factors, including social support, knowledge about HIV/AIDS and ARVs, stigma and discrimination, drug side effects, and the complexity of the treatment regimen. Interventions targeting these risk factors may help improve patient compliance and achieve more optimal treatment outcomes.